The German Socio-Economic Panel (GSOEP) after More than 15 Years: Overview - SOEP Group (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
The German Socio-Economic Panel (GSOEP) is an interdisciplinary longitudinal study of private households for the representative analysis and interpretation of social and economic behavior in the Federal Republic of Germany. As a longitudinal survey, the GSOEP primarily aims to collect information on stability and changes over time at the micro level of individuals, households and families. Because the survey period is sufficiently long, due to the design of the GSOEP, the data can also be used for analyzing intergenerational relationships. The GSOEP is an element of the statistical infrastructure born by the scientific community in compliance with international standards.
Keywords: 330; Mikroökonometrie; Panelforschung; Stichprobenverfahren; Deutschland; Laufende Stichprobenerhebung